(untitled) - Tsuchida, Kyoson (London, 1927)
This book pioneer essay intended to introduce the western world to the present day philosophy of the Far East, and to explain the basis of this philosophy.
Keywords: Triết học,Philosophy; Lịch sử,History; Nhật Bản,Japan